Optimization of the production conditions of the lipase produced by Bacillus cereus from rice flour through Plackett-Burman Design (PBD) and response surface methodology (RSM). (December 2016) - Vasiee, Alireza; Behbahani, Behrooz Alizadeh; Yazdi, Farideh Tabatabaei; Moradi, Samira
Abstract: In this study, the screening of lipase positive bacteria from rice flour was carried out by Rhodamin B agar plate method. Bacillus cereus was identified by 16S rDNA method. Screening of the appropriate variables and optimization of the lipase production was performed using Plackett-Burman design (PBD) and response surface methodology (RSM). Among the isolated bacteria, an aerobic Bacillus cereus strain was recognized as the best lipase-producing bacteria (177.3 ± 20 U/ml). Given the results, the optimal enzyme production conditions were achieved with coriander seed extract (CSE)/yeast extract ratio of 16.9 w/w, olive oil (OO) and MgCl2 concentration of 2.37 g/L and 24.23 mM, respectively. In these conditions, the lipase activity (LA) was predicted 343 U/mL that was approximately close to the predicted value (324 U/mL), which was increased 1.83 fold LA compared with the non-optimized lipase. The kinetic parameters of Vmax and Km for the lipase were measured 0.367 μM/min.mL and 5.3 mM, respectively. The lipase producing Bacillus cereus was isolated and RSM was used for the optimization of enzyme production. The CSE/yeast extract ratio of 16.9 w/w, OO concentration of 2.37 g/L and MgCl2 concentration of 24.23 mM, were found to be the optimal conditions of the enzyme production process. LA at optimal enzyme production conditions was observed 1.83 times more than the non-optimal conditions. Ultimately, it can be concluded that the isolated B. cereus from rice flour is a proper source of lipase. Highlights: Bacillus from rice flour is a proper source of lipase. RSM was used successfully as an efficient technique to optimize the enzyme production by B. cereus . PBD was used successfully as an efficient technique to optimize the enzyme production by B. cereus . 16S rDNA is a good method for the identification of pathogenic bacteria.